1998
DOI: 10.1200/jco.1998.16.2.470
|View full text |Cite
|
Sign up to set email alerts
|

p53 protein accumulation and response to adjuvant chemotherapy in premenopausal women with node-negative early breast cancer.

Abstract: p53 accumulation was associated with a poor response to one perioperative course of FAC chemotherapy. Ki-67, ER-IA, and age are important prognostic factors in premenopausal women with node-negative breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
3
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(63 citation statements)
references
References 29 publications
1
58
3
1
Order By: Relevance
“…In this series, we have shown previously that premenopausal node-negative breast cancer patients whose tumours show p53 accumulation have a poor response to one cycle of adjuvant chemotherapy, whereas patients whose tumours have no accumulation of p53 benefit from adjuvant chemotherapy. In addition, we showed Ki-67 overexpression, negative ER status, and young age (o43 years) to be associated with worse prognosis (Clahsen et al, 1998). apy given directly after surgery yields better results in terms of treatment outcome than surgery alone.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…In this series, we have shown previously that premenopausal node-negative breast cancer patients whose tumours show p53 accumulation have a poor response to one cycle of adjuvant chemotherapy, whereas patients whose tumours have no accumulation of p53 benefit from adjuvant chemotherapy. In addition, we showed Ki-67 overexpression, negative ER status, and young age (o43 years) to be associated with worse prognosis (Clahsen et al, 1998). apy given directly after surgery yields better results in terms of treatment outcome than surgery alone.…”
mentioning
confidence: 73%
“…Previously, tumour sections had been stained and analysed for oestrogen and progesterone receptor status, Ki-67 positivity, P53 expression, HER2 expression, and mitotic index (Clahsen et al, 1998).…”
Section: Other Tumour Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…It also appears that Topo IIa expression is often correlated to Her-2/neu overexpression in breast carcinoma. This complex relationship between the two genes may explain the altered sensitivity to anthracyclines of Her-2/neu-amplified breast carcinomas (Bitran et al, 1996;MacGrogan et al, 1996a;Niskanen et al, 1997;Clahsen et al, 1998;Jarvinen et al, 1998;Paik et al, 1998;Thor et al, 1998;Vincent-Salomon et al, 2000). Most previous studies regarding the effect of Topo IIa poisons in relation to the cellular level of Topo IIa expression were either performed in vitro or on breast tumour fragments without analysis of the direct in vivo effect (Gudkov et al, 1993;Asano et al, 1996a, b;Vassetzky et al, 1996;Withoff et al, 1996a, b;Zhou et al, 1999;Stacey et al, 2000).…”
mentioning
confidence: 99%
“…Some immunohistochemical studies have indicated that p53 accumulation does not predict a survival benefit with chemotherapy (1,9,10). In the study by Elledge et al (1), the patients were randomly selected to adjuvant chemotherapy or no systemic treatment.…”
Section: Discussionmentioning
confidence: 99%